Responses to the contributors - Garrett Barden (Nordicum-Mediterraneum, 2011)
A set of responses to the papers on Garrett Barden's and Tim Murphy's book Law and Justice in Community (Oxford: OUP, 2010) published in this special issue of Nordicum-Mediterraneum.